Johnson, C., Toly, N. and Schroeder, H. (eds.): The Urban Climate Challenge: Rethinking the Role of Cities in the Global Climate Regime (Cities and Global Governance). London-New York, Routledge, 2015. 258 p. - Pieczka, Ildikó (Hungarian Geographical Bulletin, 2016)
-